Main difficulties in dental care for patients with Autism Spectrum Disorder - Literature review (Research, Society and Development, 2024)
Dental care for patients with Autism Spectrum Disorder (ASD) faces challenges due to communication difficulties, and sensory and behavioral issues, which increase the risk of oral problems. The shortage of trained professionals worsens this situation, as only a small proportion of dentists are prepared to meet these needs. For effective care, it is necessary to adapt the clinical environment, apply behavioral management techniques and, in severe cases, resort to sedation. Continuous training of professionals and working in multidisciplinary teams are essential to improve the care and quality of patient's life. This study aims to analyze the difficulties in accessing dental care for patients with ASD, evaluate the training of professionals and clinical practices, and suggest strategies to improve this service. The methodology includes a qualitative literature review, and an analysing of studies published from databases such as PubMed, Google Scholar, and Scielo. To improve the quality of care, it is necessary to invest in the ongoing training of dental professionals, emphasizing inclusive practices and specific techniques for ASD.